2021
DOI: 10.1101/2021.08.24.457539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pericyte control of pancreatic islet blood flow impacts glucose homeostasis

Abstract: The pancreatic islet depends on blood supply to efficiently sense plasma glucose levels and deliver insulin and glucagon into the circulation. Long thought to be passive conduits of nutrients and hormones, islet capillaries were recently found to be densely covered with contractile pericytes, suggesting local control of blood flow. Here we determined the contribution of islet pericytes to the regulation of islet blood flow, plasma insulin and glucagon levels, and glycemia. Selective optogenetic activation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Although a 200 µm diameter fiber optic was used to activate ChR2, we cannot exclude some off target effects on smooth muscle cells. Notably, manipulation of pericyte activity through optogenetic stimulation in vivo reduced local blood flow, consistent with previous reports ( 16 , 17 ). This was unlikely due to local heating effects or damage, since termination of laser stimulation allowed blood flow to recover.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Although a 200 µm diameter fiber optic was used to activate ChR2, we cannot exclude some off target effects on smooth muscle cells. Notably, manipulation of pericyte activity through optogenetic stimulation in vivo reduced local blood flow, consistent with previous reports ( 16 , 17 ). This was unlikely due to local heating effects or damage, since termination of laser stimulation allowed blood flow to recover.…”
Section: Discussionsupporting
confidence: 92%
“…We first sought to investigate alterations in islet pericyte morphology following HFD feeding. We used mice expressing DsRed under the control of the NG2 promoter (NG2DsRed) ( 16 , 30 , 37 ), since NG2DsRed cells extensively cover islet capillaries ( Figure 1A ) ( 16 , 17 ). We found that most NG2DsRed cells expressed the pericyte marker platelet-derived growth factor receptor beta (PDGFRβ) ( Figure S1A ) ( 16 ), and a subset of them also expressed the contractile smooth muscle actin protein (αSMA) ( Figure S1A ), consistent with previous studies that described the heterogeneous nature of the pericyte population in islets ( 16 , 17 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations